2011
DOI: 10.1080/17439760.2011.558847
|View full text |Cite
|
Sign up to set email alerts
|

Flourishing students: A longitudinal study on positive emotions, personal resources, and study engagement

Abstract: Full terms and conditions of use: http://www. informaworld.com/terms-and-conditions-of-access.pdf This article may be used for research, teaching and private study purposes. Any substantial or systematic reproduction, re-distribution, re-selling, loan or sub-licensing, systematic supply or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
169
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 243 publications
(214 citation statements)
references
References 51 publications
16
169
0
8
Order By: Relevance
“…These findings suggest that it is worthwhile to actively promote positive emotion rather than simply remediating distress (Lyubomirsky, King & Diener, 2005). Studies in college settings find that students who experience positive emotion study more, and students who study more then experience further positive emotion (Ouweneel, Le Blanc & Schaufeli, 2011). Furthermore, there appears to be significant room for improvement; an estimated 21% of college students report high well-being, that 21% works harder and does better in school compared to the 19% who report low well-being or the 60% who fall somewhere in between (Howell, 2009).…”
Section: Group-based Resilience Interventions In College Freshmenmentioning
confidence: 97%
“…These findings suggest that it is worthwhile to actively promote positive emotion rather than simply remediating distress (Lyubomirsky, King & Diener, 2005). Studies in college settings find that students who experience positive emotion study more, and students who study more then experience further positive emotion (Ouweneel, Le Blanc & Schaufeli, 2011). Furthermore, there appears to be significant room for improvement; an estimated 21% of college students report high well-being, that 21% works harder and does better in school compared to the 19% who report low well-being or the 60% who fall somewhere in between (Howell, 2009).…”
Section: Group-based Resilience Interventions In College Freshmenmentioning
confidence: 97%
“…Thus far, empirical studies have not demonstrated the independent effect of hope on engagement. However, several longitudinal studies have shown that psychological capital (Luthans, 2002), consisting of self-efficacy, optimism, resilience, and hope, was positively related to work engagement among employees (Avey et al, 2010) and students (Ouweneel et al, 2011). On a daily basis, optimism, self-esteem, and self-efficacy were significantly related to work engagement (Tims et al, 2011;Xanthopoulou et al, 2008Xanthopoulou et al, , 2009a.…”
Section: Building Towards Engagementmentioning
confidence: 99%
“…Despite this theoretical reasoning, hope has never been considered as a single predictor of work engagement, neither in survey research nor in diary studies. The predictive role of positive emotions on engagement has not received much attention either, with a few exceptions (Avey et al, 2008;Ouweneel et al, 2011). Therefore, Gallagher and Lopez (2009) and Magaletta and Oliver (1999) state that longitudinal research is needed on establishing hope's predictive value for well-being.…”
Section: Work Engagement: An Individual Perspectivementioning
confidence: 99%
“…In a recent study, it was found that optimistic students were more academically engage that non-optimistic ones (Ouweneel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%